LEGENDA PULAU KEMARO : STUDI PANDANGAN PENGUNJUNG DAN HUBUNGANNYA DENGAN AYAT-AYAT KEIMANAN - John Supriyanto (Jurnal Ilmu Agama: Mengkaji Doktrin, Pemikiran, dan Fenomena Agama, 2018)
This paper is directed to find out how the views of the visitors who come to the island of Kemaro and connect it with the verses of faith that exist in the Qur'an. As is known, Kemaro Island store legends and love stories between Prince Tan Bun An and Princess Siti Fatimah. In the legend, the island of Kemaro is believed to have been formed due to the death of princes and princesses who drowned in the Musi River as a result of saving their wealth. The view of the visitors who come to this island which will then be connected with the verses of faith-as it is in the Quran-for the Quran actually speaks of a legend. In principle, the verses of faith that exist in the Qur'an does invite humankind to always mentauhidkan God in all aspects; good for world life or religion. In substance, the verses of faith invite men to always believe in God; not associating with Him; and always worship and surrender only to Him. Therefore, the motives and intentions of the visitors who come to the island of Kemaro is intended for a vacation; not worship. The opposite happened with the Chinese community and Confucian believers who came to worship and pray for the souls of their ancestors or gods that they believed.